2008
DOI: 10.1080/13854040701440493
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of IQ to Effort Test Performance

Abstract: The relationship between IQ and nine effort indicators was examined in a sample of 189 neuropsychology clinic outpatients who were not in litigation or attempting to obtain disability. Participants with the lowest IQ (50-59) failed approximately 60% of the effort tests, while patients with an IQ of 60 to 69 failed 44% of effort indicators, and individuals with borderline IQ (70 to 79) exhibited a 17% failure rate. All patients with IQ < 70 failed at least one effort test. Cutoffs for the Warrington Recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 22 publications
4
45
0
2
Order By: Relevance
“…These findings are consistent with Morra et al (2015) who reported a significant correlation between full-scale IQ and scores on the RBANS effort index. Although the use of effort tests are thought to be valid indicators of performance in individuals with low or borderline intellectual functioning, there is evidence to suggest their use with neurological patients (e.g., epilepsy) with low or borderline intellectual functioning results in a significant increase in effort test failures, even when participants lack of identifiable incentive for feigning cognitive impairment (Dean et al, 2008). Similarly, our results suggest people with SZ who have below average IQ may have a higher likelihood of failing effort measures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings are consistent with Morra et al (2015) who reported a significant correlation between full-scale IQ and scores on the RBANS effort index. Although the use of effort tests are thought to be valid indicators of performance in individuals with low or borderline intellectual functioning, there is evidence to suggest their use with neurological patients (e.g., epilepsy) with low or borderline intellectual functioning results in a significant increase in effort test failures, even when participants lack of identifiable incentive for feigning cognitive impairment (Dean et al, 2008). Similarly, our results suggest people with SZ who have below average IQ may have a higher likelihood of failing effort measures.…”
Section: Discussionmentioning
confidence: 97%
“…Effort test performance has traditionally been thought to be immune to the effects of low IQ (Flaro et al, 2007); however, there is some evidence that IQ may in fact be highly predictive of insufficient effort in neuropsychiatric populations. For example, Dean et al (2008) found that IQs in the borderline or lower range of intellectual functioning (<80) were associated with elevated rates of effort test failure in a sample of epilepsy patients. IQs in the <80 range are not uncommon in SZ (Aylward et al, 1984); however, it is unclear whether SZ patients with low IQ are at increased likelihood of failing effort testing.…”
Section: Introductionmentioning
confidence: 96%
“…Tendo em consideração os comentários formulados relativamente às percentagens de sujeitos incorrectamente classificados como "simuladores", em casos provenientes de populações clínicas, e reportando aos valores de especificidade calculados, os dados obtidos convergem com os estudos que documentam uma baixa especificidade da prova em populações com Demência (Dean, Victor, Boone, Philpott, & Hess, 2009;Hays, Emmons, Stallings, 2000;Philpott, 1992;Schretlen et al, 1991) ou outro tipo de défices cognitivos, como é o caso da Deficiência Mental (Dean, Victor, Boone, & Arnold, 2008;Goldberg & Miller, 1986;Hurley & Deal, 2006;Marshall & Happe, 2007).…”
Section: Discussionunclassified
“…For example, the authors note that Langeluddecke and Lucas (2003) apparently identified severe pain as etiological in failed SVTs in their sample, when in fact research has shown that acute (Etherton et al 2005a, b) and chronic pain (Iverson et al 2007) do not lead to effort test failure. Available data indicate that multiple SVT failures in individuals applying adequate effort appears to be confined to patients who meet criteria for dementia (Dean et al 2009) and/or have low IQ scores (Dean et al 2008;Victor and Boone 2007), or perhaps in some severe somatoform patients.…”
Section: Criticism Of Criterion D: Behaviors Meeting Necessary Critermentioning
confidence: 96%